Flexible Composite of S/PAN/C Nanofibers by Electrospinning as Binder–Free Cathodes for Li-S Batteries - Kalybekkyzy, Sandugash; Mentbayeva, Almagul; Bakenov, Zhumabay (The 6th International Conference on Nanomaterials and Advanced Energy Storage Systems. Institute of Batteries LLP, Nazarbayev University, and PI “National Laboratory Astana”., 2018)
As one of the most promising energy storage devices, lithium-ion batteries (LIBs) have attracted tremendous attention for its high volumetric and gravimetric energy density, no memory effects, good shape versatility, and relatively slow self-discharge rates. Conventional LIBs based on intercalation cathodes, have limited energy densities. Therefore, lithium/sulfur (Li/S) battery is considered as an attractive and promising candidate to be utilized for the mentioned purposes, which is due to its high theoretical specific capacity of 1672 mAh g− 1 and theoretical energy density of 2600 Wh kg-1 [1,2]. However, practical application of Li/S batteries is hindered by several drawbacks as: the electrical-insulating nature of sulfur results in its low utilization; lithium polysulfides intermediate products of electrochemical process are easily soluble into the organic electrolytes, which leads to severe capacity fading and low coulombic efficiency.
Keywords: Lithium-ion batteries (LIBs); polyacrilonitrile (PAN); carbon nanotube (CNT)